Value-based banking in CEE countries - ecological point of view - Bogna Janik (Institute of Economic Research (IER), 2017)
Banks play an important role connected with financing pro-ecological investments made by enterprises. They support pro-ecological activities of the entities applying for financing or offer saving/investment products relating to the environmental impact. In terms of their external pro-ecological activities there can be distinguished two groups of banks. The first group offers a wide selection of products and pro-ecological services as well as uses the tools of environmental risk management. The second group concentrates on offering selective products and services as well as is active in the area of pro-ecological marketing. The main objective of the study is to identify and assess some chosen aspects of ecological activities of the banks listed on Stock Exchanges in CEE countries and included in sustainable indices such as: RESPECT, CEERIUS and VONIX. The scope of this analysis encompasses selected dimensions illustrating banks' activities in terms of environmental protection. The analysis of the investigated dilemma was based mainly on the desk research of digital and documentary sources. The results indicate relatively huge differences across environmental care in value-based banks compared to conventional banks, and small differences between value-based banks themselves.
Keywords: G21; Q01; Q56; 330; value-based banking; social banking; environmental care; sustainable indices